Identification of the leading factors of the external and internal microenvironment influence on the economic performance of implementing the innovation strategy for enterprises participating in construction - Chupryna, Iu.; Mukhin, A.; Gura, Ye.; Gura, O.; Borodavka, O. (Ways to Improve Construction Efficiency, 2023)
The article is devoted to the study of the key factors of the external and internal microenvironment that influence the economic performance of implementing innovation strategies in the activities of enterprises participating in construction. In today's conditions of an unstable economic environment, globalization of markets and increased competition, an important task for enterprises is not only adaptation to changes, but also the formation of innovation strategies that contribute to the long-term effectiveness of their activities. The main task is to identify the leading factors that shape both the external and internal environment of the enterprise, with the subsequent determination of their impact on the success of implementing innovation strategies in the construction sector. To achieve this goal, an analysis of modern scientific approaches to studying influence factors was conducted, the specifics of the construction industry were determined, which determines the uniqueness of its enterprises in the context of innovation activity, and mechanisms for integrating environmental analysis into the strategic planning process were proposed. Particular attention was paid to such elements of the external environment as economic, political, social and technological factors that determine the availability of resources, regulatory support, the level of innovation culture and the degree of technological development. In the internal environment, the main elements that affect performance are the organizational structure, human resources, financial resources, the level of innovation readiness and the internal culture of the enterprise. Based on a comprehensive approach to analyzing the microenvironment of enterprises, a theoretical basis was formed for making effective management decisions regarding the choice of innovation strategies. The article also offers recommendations for construction company managers aimed at increasing adaptability to external changes, optimizing internal processes and developing sustainable innovative development strategies.